HUBUNGAN INTERTEKSTUAL ANTARA NOVEL DI BAWAH LINDUNGAN KA’BAH KARYA HAMKA, BERMANDI CAHAYA BULAN KARYA A. ASJIMY, DAN SITI NURJANAH KARYA SUNARYONO BASUKI - Yudianti Herawati (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2016)
This research aims to describe intertextuality in three novels, Di Bawah Lindungan Ka’bah, Bermandi Cahaya Bulan, and Siti Nurjanah, so that these novels’ transformation is more vivid especially the structure of the story, like motifs and sujet, characters and characterization, and the story background. It focuses on the division of motifs in the novels. It is a qualitative research and the data collection method is descriptive qualitative. It uses intertextuality theories. The analysis shows that intertextuality in Di Bawah Lindungan Ka’bah, Bermandi Cahaya Bulan, and Siti Nurjanah novels describes a clear meaning of the entanglement structure which is about equation, difference, and opposition. It also reveals plots in the motifs of each characterization.